Asia Agricultural Market: Methodology for Complete Use of Economic Resources through Supply Chain Optimization - Tlektes Espolov; Aidos Espolov; Bakyt Kalykova; Nurdaulet Umbetaliyev; Maira Uspanova; Zhenisbek Suleimenov (International Journal of Supply Chain Management, 2020)
Abstract— Agriculture remains the main sector of the Central Asia economy. The level of involvement in global production networks significantly affects the economic growth of Asian countries. The main objective of the article is to assess the opportunities for implementation of economic resources in the Asia agricultural market through supply chain optimization. After the systematization of secondary information, the study analyzes the agriculture value added, the Logistics Performance Index (LPI), and its interrelationships with economic development. This research uses statistics from open data sources as a foundation for descriptive analysis of Asian agricultural sector. The LPI, gross domestic product (GDP) per capita and the agriculture value added indicators are used to evaluate the results. The current research indicates that an effective supply chain is of great importance to agricultural sector development. However, the successful implementation of a supply chain into the agricultural sector continues to be problematic. Consequently, the issues of integration, infrastructure development, and information management require a solution.